Request to fix VAT & AIT rate as 7% for additional works of BRAC University new campus project - BUCG-ABC Joint Venture (Brac University, 2023)
This record consists of general correspondence regarding request to fix VAT & AIT rate as 7% for additional works of BRAC University new campus project.